DEVELOPING CORN VALUE CHAINS OF MINORITY ETHNIC HOUSEHOLDS IN LAO CAI PROVINCE, VIETNAM - Ho, Kim; Hien, Nguyen; Anh, Nguyen; Ninh, Ho (Tạp chí Khoa học Nông nghiệp Việt Nam, 2025)
This study focused on analyzing corn value chains in Lao Cai province as well as proposing solutions to upgrade the corn value chains in order to improve the livelihoods of ethnic minorities in Lao Cai. The study used data from a survey of 120 corn ethnic minority households and corn value chain actors in Lao Cai in 2016. Descriptive statistics, comparative statistics, and the values chain analysis method ​​are the main methods used in the study. Research results showed that farmers used outdated cultivation techniques, especially ethnic minority households in upland communes, and often produced corn by extensive farming methods (no fertilizer or a small quantity of fertilizer) with unsecured technical procedures. The product distribution channel is long with many stakeholders. Nearly 75% of the corn producers sell their products to traders in their commune who then sell it to three other levels of agents (the district, province) before the products reach the consumer.